Implementation of Information Technology in Human Resource Management:Systematic Analysis of Approaches and Challenges - Tengku Indra (Penelitian dan Pengembangan Ilmu, 2024)
The integration of Information Technology (IT) in Human Resource (HR) Management has become crucialin enhancing organizational efficiency and effectiveness. This study aims to explore the factorsinfluencing the success of IT implementation in HR management and analyze effective approaches andchallenges. Through a systematic literature review approach, we analyzed various international sourcesto understand key factors related to the integration of IT in HR management. The findings highlight theimportance of leadership support, organizational readiness, adequate IT infrastructure, employeeeducation and training, change management, effective communication, as well as measurement andevaluation of IT implementation success in HR management. These findings provide valuable insights forpractitioners and researchers to design more effective strategies in adopting IT in the context of HRmanagement.